A Review on Flat Slab Punching Shear Reinforcement (Journal of University of Babylon for Engineering Sciences, 2019)
Flat slab system is a concrete plate propped on columns without the existence of beams. During the former century, flat slabs have been used widely in different building types. In general, flat slabs are made from brittle materials and also have a finite depth; thus, flat slabs may undergo to fail due to punching shear or high deflections. Therefore, these criteria should be considered in the design of flat slabs and ignoring both of them had led to several crumbling down to many constructions in the past. To enhance the flat slab performance against failure due to punching and deflections, additional reinforcement should be supplied in the column region. In this paper, a review is presented to study the mechanism of punching shear in flat slabs and describe different types that used for reinforcement against punching shear.